EKSTRAKSI METABOLIT SEKUNDER DAN UJI ANTIOKSIDAN DARI DAUN MEDANG PERAWAS (Litsera Odorifera val) DENGAN METODE 1,1-DIPHENYL 2-PICRYLHIDRAZYL (DPPH) - I Nyoman Candra; Theo Kuntara; Agus Sundaryono (University of Bengkulu, 2022)
Litseaodoriferaval.(MedangPerawas) is well recognized in Muko-Mukoregency, Bengkulu Province and used as construction material. In Serawai and Lembak Ethnic groups, it is traditionally used as medication for mouth sprue, stomachache,and boil as well as used for inducing lactation. This research aims to extract secondary metabolite compound group contained in Litseraodorifera val. leaf and to examine its antioxidant activity potency against 1,1-diphenyl 2-picrylhidrazyl (DPPH). A Fresh leaves from Litseraodorifera val. collected from Tahura Forest, Central Bengkulu area were separated into two parts: one run into chemical screeningand the second was used for extraction experiment using ethanol, ethyl acetate, hexane and acetone. Secondary metabolite compound groups contained in those extracts were tested for antioxidantactivity potency. The results showed that the extract of Litseraodorifera val. leaf contained compound group of flavonoid, saponin, tannin, phenolicand terpenoid. The extract of Litseraodorifera val. Leafincrude extract, ethyl acetate, acetone, ethanol and hexane can reduce free radical of DPPH with IC50 of 250.7; 66.7; 69.7; 100.3 and 181.9 ppm respectively. Those are higher compared to vitamin C whose IC50 was 28.3 ppm. The extract of Litseraodorifera val. leaf haspotency as antioxidant activity that can be developed through further research.